Peran zakat dalam ekonomi syariah: Kontribusi serta dampaknya pada kesejahteraan sosial - Effendy, Maidany (Maliki Interdisciplinary Journal, 2024)
The Role of Zakat in Islamic Economics: Its Contribution and Impact on Social Welfare. Zakat is an asset that, in accordance with Islamic law, must be given to those entitled to receive it by a Muslim or business entity. Zakat has a direct relationship with economic principles, and its management can have a significant impact on people’s economic life. One of the main objectives of zakat in Islamic economics is to reduce economic inequality. This research uses descriptive qualitative research or library research. The practice of zakat reflects the principles of justice and social solidarity which are the basis in Sharia economics and equitable distribution of wealth, with the ultimate goal of realizing social welfare and economic stability. In its implementation, zakat has significant benefits in overcoming inequality in the distribution of wealth in society. By changing the way wealth is distributed from the rich to the poor, so that the practice of zakat can affect economic inequality. The purpose of writing this article is to provide a basic understanding of Zakat as a key principle in Sharia economic law, the role of zakat in reducing economic inequality and supporting social welfare and understanding the differences between the zakat system and conventional taxation.